Construction Strategy of Elderly Care Service Facilities Planning System in Old Industrial Residential Areas - Feng Qiao (Forest Chemicals Review)
Based on the investigation of the existing problems of various service facilities in China’s elderly care community at the present stage, the research systematically analyzes the service facilities at the hardware level, such as road traffic, facility layout, green space planning, and the service facilities at the software level, such as communication space, health care space, living space, etc, On the one hand, it constructs the optimization strategy system of elderly care community service facilities, on the other hand, it puts forward constructive optimization strategies, so as to provide a reference basis for building an elderly care community that meets the needs of the new era.